How Are Insecticide-Treated Bednets Used in Ugandan Households? A Comprehensive Characterization of Bednet Adherence Using a Remote Monitor - Krezanoski, Paul J.; Santorino, Data; Agaba, Alfred; Dorsey, Grant; Bangsberg, David R.; Carroll, Ryan W. (The American Journal of Tropical Medicine and Hygiene, 2019)
Long-lasting insecticide-treated bednets are widely used and promoted for malaria control. Limitations in measurement methods have resulted in a poor understanding of how bednets are used in practice. We deployed a novel remote monitoring tool in Uganda to obtain, for the first time, a comprehensive characterization of bednet use in households at risk for malaria. Ten households each used one SmartNet adherence monitor over a commonly used sleeping area for 6 weeks. SmartNet continuously measures and records bednet use every 15 minutes. Bednet use was monitored for a total of 9,258 hours overall, with an average of 42 nights per household (SD: 3.5). Average duration of bednet use was 9 hours 49 minutes per night (SD: 1 hour 56 minutes), and adherence was 85–90% from 2100 to 0600. Bednets were not used at all on 4.5% (19/418) of observation nights. Overall, the average clock time that bednets were unfurled was 2034 (SD: 1 hour 25 minutes) and they were folded up at 0743 (SD: 43 minutes). The rate of interruptions per night observed in all households was 0.23 (86/369), with an average duration of 48 minutes (SD: 49 minutes). There was substantial heterogeneity between households, and some households had consistently poorer adherence relative to others. Variations in bednet use behaviors are a potentially important, and under-researched, component of long-lasting insecticide-treated bednet effectiveness. Remote bednet use monitors can provide novel insights into how bednets are used in practice, helping identify both households at risk of malaria due to poor adherence and also potentially novel targets for improving malaria prevention.
Keywords: Insecticide-Treated Bednets; Ugandan Households; Bednet Adherence; Remote Monitor